Asset assessments and community social work practice - Delgado, Melvin; Humm-Delgado, Denise (New York : Oxford University Press, 2013)
The role and importance of assessment in development of health and social services are well accepted in the field, and represent the fundamental building blocks for the creation of any form of social intervention. Need assessments are, without question, the most common form of assessment in these fields. This book explores asset assessments and community social work practice.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Social service; Community organization; Community health services -- Planning